SCIENCE LEARNING MODEL TO IMPROVE NATURALIST INTELLIGENCE FOR EARLY CHILDHOOD - Siti Fatonah; ZUHDAN KUN PRASETYO (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2017)
This research aims to commonly analyze the implementation model of science learning for early childhood, and presets the illustration about naturalist intelligence on early childhood. This research is also explained the effectiveness from the implementation model of science learning to improve naturalist intelligence in TK (Kindergarten) Masjid Syuhada Yogyakarta. This research uses qualitative research method which is directed to field research. The data that are used to this research are obtained from observation, collecting from field, interview, and documentation. Based on the research result, it can be concluded that; Firstly, the methods in implementing the science learning for early childhood in TK Masjid Syuhada use methods such as playing, telling story, exemplary, habituation, excursion, demonstration, project and question and answer method. Secondly, naturalist intelligence that can be seen from the science learning is that the children can identify animals and plants around them, they have high interest to the others and nature preservation, love about farming, care to the pets, love to have excursion in nature, love to study about nature, animals as well as plants. Third, the effectiveness in the implementation of science learning to improve children’s naturalist intelligence is curriculum improvement in TK Masjid Syuhada. They are intracurricular and extracurricular learning and basic learning that including basic education in TK Masjid Syuhada as well as evaluation. Effectiveness of science learning can be seen from the evaluation of children’s learning result and their expression, enthusiasm or sprit of the children when following every learning process given by the teacher, and the materials that are supporting the learning process as well as the creativity and innovation of the teacher.